The Development of Collaborative Learning in The Frame work of Learning Developmnet HE 4.0 - Tjahjono; Susanto; Yulhendri (International Journal of Science, Technology & Management, 2020)
This study reports the development of an adaptive collaborative learning framework in the industrial era 4.0. The development of learning models in schools is determined by the ability of teachers in pedagogy and the ability of the technology used. The purpose of this study is to develop a collaborative learning model in terms of student-centered learning in addition to interactive learning that will determine the success of the learning management system. Respondents of this study were 310 primary school teachers in West Jakarta, DKI Jakarta Province. The research methodology used the Structured Equation Model (SEM), Obtained by using the fit model testing 72.01% and 66.45% and r square as much as 110.86% and 94.16% for the parameters of Collaborative Learning and Learning Management System. This study uses a standard loadings factor of 0.7. The results showed that all loadings factor values for each indicator were> 0.7. Research findings indicate an influence between interactive learning, collaborative, user-centered learning, and learning management systems.